Homenaje a nuestros artistas : Bruno Abdulio Giudici, Alberto Musso, Marcelo Santángelo, Eduardo Tejón, Ricardo Scilipotti - González Moretti, Leticia; Juárez, Iris Mabel; Benchimol, Silvia; Zaragoza, María Inés (Universidad Nacional de Cuyo. Facultad de Artes y Diseño. Dirección de Investigación y Desarrollo, 2010)
Fil: González Moretti, Leticia. Universidad Nacional de Cuyo. Facultad de Artes y Diseño